Cross-Sectional Assessment of Nutritional Status, Dietary Intake, and Physical Activity Levels in Children (6–9 Years) in Valencia (Spain) Using Nutrimetry - Morales-Suárez-Varela, María; Peraita-Costa, Isabel; Llopis-Morales, Agustín; Llopis-González, Agustín (Nutrients, 2024)
The aims of this research were to evaluate the current nutritional status, dietary intake, and level of physical activity and assess the need for intervention. This was a cross-sectional study with 2724 participating children aged 6–9 years old. Nutritional status was assessed using nutrimetry, dietary intake with a 3-day food-recall questionnaire and physical activity with an ad hoc questionnaire. The nutricode with the highest prevalence was healthy weight/normal stature, with 51.3% of the sample. For the BMI for age Z-score, those in the overweight/obesity category represented 37.5% of the sample, while the thinness category included 7.6%. Intake of calories, proteins, sugar, lipids, SFA, MUFA, and cholesterol were significantly higher than recommended. The thinness groups consumed a significantly higher amount of excess calories while the overweight/obesity groups had the lowest mean excess calorie intake. Children in the thinness category presented the highest rates at both ends of the spectrum for sedentary activities. This study showed the high prevalence of malnutrition in schoolchildren. The results for the risk of thinness and overweight/obesity according to individual nutrient intake should be carefully interpreted. Lifestyle is a fundamental aspect to consider when combating malnutrition, especially at the level of dietary and physical activity habits, to combine various methods of intervention to improve nutritional status.